ECONOMIC EFFECTS OF INVESTMENT IN IRRIGATION SYSTEMS IMPLEMENTATION AT THE SMALL FAMILY FARMS - Jeločnik, Marko; Subić, Jonel; Zdravković, Aleksandar (Economics of Agriculture, 2022)
Water is the source of life for all living beings, but also an irreplaceable input in agricultural production. According to the available water and land potentials in Serbia irrigation is used at generally negligible arable areas. Although it represents an agro-technical measure whose implementation usually causes significant investment costs for the farm, its application ensures high and stable yields of high quality crops’ fruits, while indirectly it affects increase in incomes and continuity in farm sustainability. The main goal of the paper is presenting an assessment of the effects of investing in implementation of the irrigation system (type Tifon) on a small family farm primarily active in crop farming. Investment analysis was based on basic static and dynamic methods for assessing the effectiveness of investments. The assessment was focused to two modalities in crop production, i.e. implementation of irrigation in crop farming at 25 ha and 30 ha. In both observed modalities the investment was assessed as economically justified alternative for farm business improvement, while there are shown slightly better results with the rise of used agricultural surfaces.